Impact of high-standard farmland construction on farmers’ income growth—quasi-natural experiments from China - Yusheng, Chen; Zhaofa, Sun; Yanmei, Wang; Yang, Han (Frontiers in Sustainable Food Systems, 2023)
This paper examines the impact of high-standard basic farmland construction on farmers' income in China using panel data at the provincial level from 2006 to 2021. The study aims to provide insights into the relationship between high-standard basic farmland construction and farmers' income by employing a difference-in-differences model.The research background of this study is rooted in the importance of agricultural development and rural income improvement in China. As the agricultural sector plays a crucial role in ensuring food security and rural stability, it is essential to explore the effects of high-standard basic farmland construction on farmers' income.The primary objective of this research is to estimate the impact of high-standard basic farmland construction on farmers' income and to identify any heterogeneity in this relationship across different regions and income levels. By analyzing the baseline regression results, the study finds a significant positive effect of high-standard basic farmland construction on farmers' income.To gain a deeper understanding of the mechanisms underlying this relationship, the study conducts further analysis on the impact pathways. The findings suggest that high-standard basic farmland construction enhances farmers' income through improvements in agricultural production conditions, land transfer levels, and the cultivation of new agricultural management entities.Furthermore, the study explores the role of high-standard basic farmland construction in grain-producing and non-grain-producing regions. In grain-producing regions, high-standard basic farmland construction primarily increases farmers' income from family-operated businesses. Conversely, in non-grain-producing regions, it predominantly boosts farmers' income from wages and property.Overall, this research contributes to the understanding of the impact of high-standard basic farmland construction on farmers' income in China. The findings highlight the importance of promoting high-standard basic farmland construction for rural income improvement, with implications for agricultural policies and rural development strategies.